THE THE IMPACTS OF EPCS ON PRAGUE’S RESIDENTIAL MARKET RENTS (The South East European Journal of Economics and Business, 2026)
The EU has introduced legal regulations to mitigate climate change, and it is pertinent to investigate economic incentives to invest in higher Energy Performance Certificates (EPC). This paper examines the impact of EPCs on asking rents in Prague’s residential property market using a hedonic regression model. A newly collected dataset of 1,118 rental advertisements is analyzed, with control for the apartment total area, condition, location, and energy efficiency. The results indicate that more energy-efficient residential properties command a rental premium, even though the magnitude varies across location segments. In highly desirable areas, factors such as accessibility and prestige play a crucial role, while in less attractive areas, the EPC ratings are less pronounced. The findings contribute to the existing literature on the economics of energy efficiency by providing empirical evidence from a Central and Eastern European city, offering insights for policymakers, investors, and tenants.